Organohalogenated contaminants (OHCs) in high-altitude environments: A review and implication for a black carbon relationship. Issue 13 (3rd July 2017) - Ali, Usman; Sweetman, Andrew James; Riaz, Rahat; Jones, Kevin C.; Malik, Riffat Naseem
ABSTRACT: Organohalogens contain important groups of persistent organic pollutants that have a special focus owing to their adverse effects. Due to long-range atmospheric transport, these chemicals could reach to higher altitude cold regions where they become deposited and trapped on surface media, i.e., soil, water, sediments, and snow. Intriguingly, another pollutant, black carbon (BC) shows a strong association with these organohalogens and could sturdily affect the environmental distribution of these contaminants. It is implicated that BC can significantly alter not only the behavior of organohalogens in the environment but its presence could also lead to an increase in temperature which may result in the rerelease of the trapped organohalogens in these regions. Hence, theories of "glacier hypothesis" and "forest filter effect" could be better explained.